(untitled) (Journal of Information Technologies in Education (ITE), 2011)
Concepts are differentiated in the article: «informative-technological jurisdiction» and «informative-methodical jurisdiction», the value of their forming turns out in the process of methodical preparation of teacher of physics, the ways of forming of informative-methodical competence of students are examined in the process of study of the special disciplines.